2003
DOI: 10.1248/jhs.49.444
|View full text |Cite
|
Sign up to set email alerts
|

Sub-chronic Toxicity Studies of the Aqueous Extract of Boerhavia diffusa Leaves

Abstract: The acute and subchronic toxicity studies of Boerhavia diffusa (B. diffusa) leaves in albino mice and rats were investigated. Phytochemical analysis was also carried out. 500, 1000 and 2000 mg/kg of the aqueous leaf extract were administered orally to the test groups while distilled water was given to the control group. The parameters measured include food and fluid intake, body weight, absolute and relative weight of various organs, haematological parameters [total white blood cell (WBC) and packed cell volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 6 publications
(4 reference statements)
2
23
0
1
Order By: Relevance
“…Shade-dried and pulverized plant material (150 g 暳 3) was successively extracted with n-hexane (BDHE), ethyl acetate (BDEA) and methanol (BDME) by continuous hot extraction using Soxhlet apparatus at a temperature for 6 hours not exceeding the boiling points of the solvents. The extracts were concentrated with a rotary evaporator (IKA, Germany) at low temperature (40- [21] .…”
Section: Extraction Of the Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shade-dried and pulverized plant material (150 g 暳 3) was successively extracted with n-hexane (BDHE), ethyl acetate (BDEA) and methanol (BDME) by continuous hot extraction using Soxhlet apparatus at a temperature for 6 hours not exceeding the boiling points of the solvents. The extracts were concentrated with a rotary evaporator (IKA, Germany) at low temperature (40- [21] .…”
Section: Extraction Of the Plant Materialsmentioning
confidence: 99%
“…It has also been reported to be useful in the treatment of elephantiasis, night blindness, corneal ulcers, various hepatic disorders and as an antiviral agent [5,6] . In Nigerian folk medicine it has been widely used for the treatment of epilepsy [7] , infertility and menstrual pain [8] .…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with results of present experiment on Chelidonium supplementation Vakil et al (1989) and Rawling et al (2009) , while Gawronska et al (2009) and Banerjee et al (2010 observed decrease in the activity of SGPT. Orisakwe et al (2003) reported statistically similar levels in B. diffusa extract administered albino rats.…”
Section: Serum Glutamate Pyruvate Transaminase (Sgpt)mentioning
confidence: 62%
“…The significant increase in ALP levels by the ethanol extract of RTF shows that possible cholestasis occurred at the dose levels tested (Orisakwe et al, 2003). This indicates slight adverse effect on the liver since AST, ALT and bilurubin levels were not significantly elevated against the control.…”
Section: Sub-acute Toxicological Assessmentmentioning
confidence: 82%